Exploring Purchase Decision of Skincare Products: The Interplay of Halal Awareness, Country of Origin, and Online Cosumer Reviews with Religiosity as A Moderating Variable - Rizki Amalia (Jurnal Ilmu Ekonomi dan Bisnis Islam, 2023)
This research aims to identify and analyze the effect of halal awareness, country of origin of, and online consumer reviews on purchase decisions for local brand skin care products with religiosity as a moderating variable. The population in this research is Muslim millennial generation consumers in the city of Palu who use local brands of skin care products. The sample size is determined using the Lemeshow formula, the reason researchers use this formula is because the population size is unknown because the number is too large and can change at any time. Based on the Lemeshow formula calculation above, the sample size was 96 people, but to avoid outliers, the sample was rounded up to 100 people. This research analysis using the SmartPLS 3 analysis tool. The results show that halal awareness, country of origin of the product, and online consumer reviews influence purchase decisions. Religiosity is able to moderate Halal Awareness and Country of Origin on purchase decisions, but is not able to moderate Online Consumer Reviews